Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-5470-145

+91 7353221155

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Q.1. (x+1)= 2*log(2^x+3)-2*log(1980-2^-x)first log has base 2 and second one has base 4. so, question is sum of roots of the  above equation(a)3954 (b)log11(base=2)  (c)log3954(base=2)Q.2. lim ((x^(x^x))-x^x) =? x tending to 0+

8 years ago

a.1)    option b

2 log(4) (1980 - 2^-x)    (4) means base  it can be written as 2/2 log(2) (1980 - 2^-x )  by log properties

putting the value 2^x = y finally we get the equation as

log {(y + 3 )}^2   - log {(1980 y -1)/y} = x + 1

logs are all base 2 now applying the log properties again we get

log [{y (y + 3)^2}/(1980y - 1)] = x + 1

y (y + 3)^2}/(1980y - 1) = 2 ^(x+1) = 2^x . 2

as 2^x = y we get

y^2 - 3954 y + 11 = 0

the roots will be in form of 2^x1 and 2^x2

there product   2^x1*2^x2 = 2^(x1+x2) = 11

x1+x2 = log (2) 11

q.2) lim x tending to 0+ x ^ x = 1

now putting this result in the limits and applying the properties of limits we get

Now you can win by answering the questions on Discussion Forum. So help discuss any query on askiitians forum and become an Elite Expert League askiitian.

Thanks and Regards

Jitender